Treatment of skeletal Class II with retrognathic mandible in growing patient using modified sagittal guidance twin-block appliance - Lubis, Hilda Fitria; Yanita, Sherliana (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Class II discrepancies were primarily perceived as sagittal problems. Class II malocclusions usually cause aesthetic and functional problems, depending on the degree of anterior-posterior mismatch and interaction with adjacent soft tissues. Purpose: This case report aimed to evaluate the effect of modified sagittal guidance twin-block (SGTB) for Class II Skeletal and Dental Changes in a growing patient. Case: A 10-year-old patient presented with her parents and complained mainly of aesthetic problems. Diagnosis showed skeletal Class II pattern (ANB 6º) with retrognathic mandible, angle Class II molar relationship, convex facial profile, lower dental midline shift, crowding in the lower anterior teeth, and incompetent lips. Case Management: A growth modification treatment plan was considered for the patient, using modified SGTB. Both bonded and removable had the same design. In the SGTB, the bite block was angled at 70º, pushed toward the occlusal plane to maximize horizontal force toward the mandible. As a result, the mandible is guided forward and optimally positioned during occlusion. Conclusion: An ideal overjet and slight correction on lower anterior crowding teeth were achieved after full-time wear of a modified SGTB for 12 months. A modified SGTB appliance is effective in treating skeletal Class II with a retrognathic mandible.